Apprendere al museo la musica come storia: didattica museale e costruzione delle conoscenze storico-musicali - Maria Rosa De Luca (Musica Docta)
The article addresses some of the main challenges related to the transmission of music-historical knowledge in today’s educational context, both at the school and academic levels. The focus is on the construction of historical knowledge, a crucial issue for the modes of historiographical narration. In this context, the analysis of teaching-learning procedures in music history extends to the music museum, understood as a space dedicated to promoting the learning of music history knowledge through innovative teaching approaches. The epistemological assumptions of didactic work are also discussed, taking into account the urgent problems that teachers face today in the process of didactic transposition, starting with the resistance to the growing phenomenon of presentism.